Activation of mitogen-activated protein kinase signaling and development of papillary thyroid carcinoma in thyroid-stimulating hormone receptor D633H knockin mice - Eszlinger Markus; Stephenson Alexandra; Mirhadi Shideh; Patyra Kondrad; Moran Michael F.; Khalil Moosa; Kero Jukka; Paschke Ralf (BioScientifica Ltd., 2025)
Objective: Nonautoimmune hyperthyroidism (NAH) is rare and occurs due to a constitutively activating thyroid stimulating hormone receptor (TSHR) mutation. In contrast to other thyroid nodules, no further evaluation for malignancy is recommended for hot thyroid nodules. In the first model for NAH in mice nearly all homozygous mice had developed papillary thyroid cancer by 12 months of age.
Methods: To further evaluate these mice, whole exome sequencing and phosphoproteome analysis were employed in a further generation of mice to identify any other mutations potentially responsible and to identify the pathways involved in thyroid carcinoma development.
Results: Only three genes (Nrg1, Rrs1, Rasal2) were mutated in all mice examined, none of which were known primary drivers of papillary thyroid cancer development. Wild-type and homozygous TSHR D633H knockin mice showed distinct phosphoproteome profiles with an enrichment of altered phosphosites found in ERK/mitogen-activated protein kinase (MAPK) signaling. Most importantly, phosphosites with known downstream effects included BRAF p.S766, which forms an inhibitory site: a decrease of phosphorylation at this site suggests an increase in MEK/ERK pathway activation. The decreased phosphorylation at BRAF p.S766 would suggest decreased AMP-activated protein kinase (AMPK) signaling, which is supported by the decreased phosphorylation of STIM1 p.S257, a downstream AMPK target.
Conclusion: The modified phosphoproteome profile of the homozygous mice in combination with human literature suggests a potential signaling pathway from constitutive TSHR signaling and cAMP activation to the activation of ERK/MAPK signaling. This is the first time that a specific mechanism has been identified for a possible involvement of TSH signaling in thyroid carcinoma development.